The Political Economy of Crypto Assets: World Dependency on Digital Financialization - Warganegara, Muhd Rafli Ramadhan (Institute of International Studies, 2024)
The massive development of technology, the use of data, and information systems have brought the popularity of crypto assets—also known as cryptocurrency—as part of the digital economy in the globalized political economy order. This study aims to capture structuralist criticisms by Karl Marx of crypto assets as a global political economy project and see its massive entanglement in the current global political order. Using the concepts of base and superstructure, this study will dismantle the discourse on the mode of production of commodities that have been questioned based on their digital and intangible commodity. It reveals the reproduction of the surplus labor process as a part of an initial understanding of how the crypto assets work from the social relations network's perspective. In further analysis, this study uses Dependency Theory to view crypto assets as a global system phenomenon that cannot escape the role of multi-sectors that perpetuate the presence of global structuralism in the current global economy. The research utilizes Critical Discourse Analysis (CDA) to investigate the intertwining relationships between crypto assets and world dependency in the international political economy order.Keywords: blockchain; cryptocurrency; dependency theory; digitalization; Global South